2000
DOI: 10.1046/j.1464-410x.2000.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Failed vasectomy reversal: is a further attempt using microsurgery worthwhile?

Abstract: Objective To determine, in failed vasectomy reversal, the usefulness of a revised anastomosis using microsurgery in achieving sperm in the ejaculate and fertility, and to relate the outcome to the site of the anastomosis, length of time from vasectomy, and presence or absence of sperm in the vas at surgery. Patients and methods In a series of 28 patients with con®rmed anastomotic obstruction undergoing vasectomy reversal (over a 10-year period), a microsurgical technique using an oblique end-to-end two-layer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…The patency and pregnancy rates we report are similar to those reported in other studies. 26,27 It is hypothesized that most cases of failed primary VV occur as a result of obstruction at the anas- tomosis site. We found that in 37 (80%) of 46 cases of repeat VV, obstruction at the anastomosis site was confirmed with either a sperm granuloma (28 of 46 cases, 61%) or a stricture of the vas deferens (9 of 46 cases, 20%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patency and pregnancy rates we report are similar to those reported in other studies. 26,27 It is hypothesized that most cases of failed primary VV occur as a result of obstruction at the anas- tomosis site. We found that in 37 (80%) of 46 cases of repeat VV, obstruction at the anastomosis site was confirmed with either a sperm granuloma (28 of 46 cases, 61%) or a stricture of the vas deferens (9 of 46 cases, 20%).…”
Section: Discussionmentioning
confidence: 99%
“…Although assisted reproductive technologies have significantly impacted the treatment of male infertility, microsurgical reconstruction of obstructed genital tracts remains the most successful, rational and cost-effective method of treating men with obstructive azoospermia due to vasectomy. 26,27 Seminal fluid contains many enzymes, including various hydrolases, which are thought to originate in the accessory reproductive structures, including the epididymis. 28 It has been previously shown that α-1-4-glucosidase disappears from the semen or decreases below 40 mU/ejaculate in men with confirmed vasectomy or genital tract obstruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most failures of vasovasosto my may arise through obstruction at the anastomotic site [14]. A long time interval followin g vasectomy [2,6] and no sperm in¯uid obtaine d from the testicular end of the vas during vasectomy reversal [1,16] was considered a negative predictive factor for patency af ter reanastomosis. A ll 6 patients who underwent reversal within 6 years of vasectomy had sperm in the postoperative ejaculate, while 3 of 12 patients who underwent reversal more than 6 years af ter vasectomy continued to have obstructive azoospermia (Figure 1) .…”
Section: Discussionmentioning
confidence: 99%
“…These men should be treated by a repeat reversal procedure rather than ART, since both patency and pregnancy rates are acceptably high after a second procedure [8].…”
Section: Prognostic Factorsmentioning
confidence: 99%